Wearing your sex on your face : the ethics of irigaray and lipstick. - Tan, Wei Si. (2012)
Little has been written about the function of costuming and makeup in films with specific focus on their play with gender and sexuality. Conventionally, for purposes of narrative cinema, costuming and makeup have been deployed to either emphasise characterisation or be used as a concealment of one’s “inner self”. In regards to female characters, Lucy Bolton observes that the emphasis on women’s physical beauty in narrative cinema has reduced their role “to one of a mere physical presence that serves to complement or define the hero” (Bolton 29). This reduction of the female presence is a result of deliberate and necessary control that stems from a patriarchal economy in order for men to define themselves as the absolute bearer of meaning.